2005
DOI: 10.1093/jn/135.3.653s
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multiple Micronutrient Supplementation for Improving Anemia, Micronutrient Status, and Growth in South African Infants1

Abstract: Growth faltering, anemia, and multiple micronutrient deficiency are common during infancy in developing countries. This South African trial was part of a multicenter study aimed at testing the efficacy of multiple micronutrient supplementation on growth, anemia, micronutrient status, and morbidity during infancy across 4 countries. A total of 265 infants aged 6-12 mo were individually randomized to 1 of 4 intervention groups: a daily multiple micronutrient supplement (DMM), a daily placebo supplement (P); a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
5
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 29 publications
10
93
5
8
Order By: Relevance
“…Other studies of multiple micronutrients (MMN) found positive effects of supplementation on growth among Mexican (Rivera et al, 2001) and Vietnamese (Thu et al, 1999;Hop and Berger, 2005) infants and among older children in Tanzania (Ash et al, 2003), suggesting that deficiency of one or more these micronutrients was limiting their physical development. Contrary to these results, multiple micronutrient (MMN) supplements did not affect the growth of children in other settings (Penny et al, 2004;Ló pez de Romaña et al, 2005;Smuts et al, 2005;Untoro et al, 2005), possibly because the study subjects were less growth restricted initially, they were not lacking in any of the specific micronutrients that are critical for growth, or the supplements that were provided were poorly absorbed.…”
Section: Introductioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Other studies of multiple micronutrients (MMN) found positive effects of supplementation on growth among Mexican (Rivera et al, 2001) and Vietnamese (Thu et al, 1999;Hop and Berger, 2005) infants and among older children in Tanzania (Ash et al, 2003), suggesting that deficiency of one or more these micronutrients was limiting their physical development. Contrary to these results, multiple micronutrient (MMN) supplements did not affect the growth of children in other settings (Penny et al, 2004;Ló pez de Romaña et al, 2005;Smuts et al, 2005;Untoro et al, 2005), possibly because the study subjects were less growth restricted initially, they were not lacking in any of the specific micronutrients that are critical for growth, or the supplements that were provided were poorly absorbed.…”
Section: Introductioncontrasting
confidence: 66%
“…Among Tanzanian school children 6-11 years of age, an MMN-fortified drink increased rates of both linear growth and weight gain (Ash et al, 2003). By contrast, there was no growth impact of MMN supplementation in a recent trial in Peru (Penny et al, 2004) or in three sites included in a recently completed multi-center trial (Ló pez de Romaña et al, 2005;Smuts et al, 2005;Untoro et al, 2005). The inconsistent results across these different sets of studies may relate to the age of the study subjects, their underlying nutritional status, the duration of supplementation, the composition of the supplements, or their mode of delivery (e.g., with or without meals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to those of three other studies of home fortification products in which there was no significant impact of the intervention on vitamin A status. 3,9,17,18 In our population, the lack of impact might be partially attributable to concurrent vitamin A capsule distribution, the insensitivity of current indicators to assess vitamin A status, 19 and the relatively low prevalence of vitamin A deficiency in the population without inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…The results of four subsequent studies adopting the IRIS (The International Research on Infant Supplementation Initiative) protocol, 6 in which daily and weekly supplementation were compared among infants, indicate that only daily supplementation is effi cacious in controlling anemia. 8,9,16,21 Prior to the present clinical trial, there was no record of a study comparing the effectiveness of daily and weekly iron supplementation in preventing anemia among infants.…”
Section: Abmentioning
confidence: 99%